HUBUNGAN KEKUATAN OTOT DENGAN TINGKAT KEMANDIRIAN LANSIA DI WILAYAH KERJA PUSKESMAS MAKKASAU KELURAHAN BULOGADING KOTA MAKASSAR - Rusli Taher; Ahmad Mushawwir (Stikes Graha Edukasi Makassar, 2021)
Objective: The purpose of this study was to determine the relationship of muscle strength to the level of independence of elderly in urban bulogading urban village. Method: The research design used was correlational design with Cross Sectional Study approach ie independent and dependent variable identified at one time unit. Population is all elderly in urban village Bulogading Makassar which amounts to 206 people by using sample selection technique by proportionate stratified randam sampling. Discussion: Muscle Strength is Muscle Strength is a force or power generated muscle or group of muscles in a maximum contraction. Muscle strength here in the intention is the ability of muscles to contract and generate power, so that in the activity or activity muscle strength has a role as a provider. Result: The result of the research shows that there is a picture of muscle strength in the working area of ??puskesmas makkasau urban village bulogading Makassar. There is an illustration of the level of independence of the elderly in the working area of ??puskesmas makkasau urban village bulogading Makassar. There is a relationship of muscle strength with the level of elderly independence in the working area of ??makkasau urban village bulogading Makassar. Conclusion: From the result of data analysis using statistical test of tau_b, so obtained significant result with value (P = 0,000) and that mean p value <0,05, hence can be concluded that H0 rejected and Ha accepted that there is correlation of muscle strength with the level of independence of elderly in the working area of ??puskesmas makkasau urban village bulogading Makassar